2016
DOI: 10.7554/elife.18447
|View full text |Cite
|
Sign up to set email alerts
|

Diverse fates of uracilated HIV-1 DNA during infection of myeloid lineage cells

Abstract: We report that a major subpopulation of monocyte-derived macrophages (MDMs) contains high levels of dUTP, which is incorporated into HIV-1 DNA during reverse transcription (U/A pairs), resulting in pre-integration restriction and post-integration mutagenesis. After entering the nucleus, uracilated viral DNA products are degraded by the uracil base excision repair (UBER) machinery with less than 1% of the uracilated DNA successfully integrating. Although uracilated proviral DNA showed few mutations, the viral g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
130
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(149 citation statements)
references
References 77 publications
19
130
0
Order By: Relevance
“…Monocytes and dendritic cells had low incision activity on the U:A substrate ( Fig. 2c), resonating with the low level of uracil base excision in monocytes 12 and confirming that myeloid lineages have unique uracil repair phenotypes 13 . However, these differences in uracil repair were not apparent for the U:G substrate, presumably due to redundant activities of SMUG1 14 and MBD4 15 in incising U:G-containing substrates.…”
supporting
confidence: 54%
“…Monocytes and dendritic cells had low incision activity on the U:A substrate ( Fig. 2c), resonating with the low level of uracil base excision in monocytes 12 and confirming that myeloid lineages have unique uracil repair phenotypes 13 . However, these differences in uracil repair were not apparent for the U:G substrate, presumably due to redundant activities of SMUG1 14 and MBD4 15 in incising U:G-containing substrates.…”
supporting
confidence: 54%
“…We also observed that around 50% of GFP Ϫ MDM harbored some amount of intranuclear HIV-1 DNA. A recent study suggested that a subset of MDM may be resistant to HIV-1 infection due to increased dUTP incorporation into HIV-1 RT products and their subsequent degradation (48). It is therefore possible that the fewer EdU puncta within the GFP Ϫ MDM subset may result from the degradation of uracilated HIV-1 RT products.…”
Section: Discussionmentioning
confidence: 99%
“…These contexts arise from two innate immune responses that result in the introduction of dUMP into viral DNA [15]. These responses involve either enzymatic cytosine deamination of the viral (-) strand cDNA by APOBEC DNA deaminases [1,2] or the incorporation of dUMP opposite to adenine on either strand of viral DNA during reverse transcription [3,4,6]. The incorporation pathway arises specifically in quiescent cells because [dUTP] is typically higher in such non-dividing cells and most DNA polymerases readily utilize dUTP as a substrate in competition with dTTP [79].…”
Section: Introductionmentioning
confidence: 99%
“…The two uracilation pathways are quite unique because cytosine deamination leads to G⍰A transition mutations at specific trinucleotide sequences on (+) strand genomic RNA [10], while dUMP incorporation opposite to adenine occurs on both strands and is not intrinsically mutagenic [3]. Previous studies by us and others indicate that the majority of the dUMP that is present with in vitro infected monocyte-derived-macrophages (MDM) arises from dUMP incorporation by reverse transcriptase [4,6]. Once the viral DNA products enter the nuclear compartment, both types of lesions are substrates for uracil excision by the enzyme nuclear uracil DNA glycosylase (hUNG2)[3], the first enzyme in the UBER pathway.…”
Section: Introductionmentioning
confidence: 99%